2021
DOI: 10.14569/ijacsa.2021.0120950
|View full text |Cite
|
Sign up to set email alerts
|

Customer Segmentation and Profiling for Life Insurance using K-Modes Clustering and Decision Tree Classifier

Abstract: Customer segmentation and profiling has become an important marketing strategy in most businesses as a preparation for better customer services as well as enhancing customer relationship management. This study presents the segmentation and classification technique for insurance industry via data mining approaches: K-Modes Clustering and Decision Tree Classifier. Data from an insurance company were gathered. Decision Tree Algorithm was applied for customer profile classification comparing two methods which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Bhatia et al studied consumer life insurance purchasing behavior and stated that researchers could apply advanced supervised and unsupervised machine learning and Artificial Neural Network methods [8]. Meanwhile, previous studies recommend employing alternative classification methods such as Random Forest, Naive Bayes, or even Artificial Neural Networks for consumer segmentation and profiling [21]. This paper will use five classification models: Decision Tree, Logistic Regression, Naïve Bayes, Random Forest, and Artificial Neural Network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatia et al studied consumer life insurance purchasing behavior and stated that researchers could apply advanced supervised and unsupervised machine learning and Artificial Neural Network methods [8]. Meanwhile, previous studies recommend employing alternative classification methods such as Random Forest, Naive Bayes, or even Artificial Neural Networks for consumer segmentation and profiling [21]. This paper will use five classification models: Decision Tree, Logistic Regression, Naïve Bayes, Random Forest, and Artificial Neural Network.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded, using data mining approaches, that segmenting customers may be accomplished. The results of consumer segmentation have been improved by implementing both clustering and classification algorithms [21]. Recent research by Pereira, K. et al [22] stated that the predictive ability of machine learning models may be hindered by privacy-preserving techniques and proved that discretization and encryption, two privacy-preserving methods, affect the accuracy of machine learning models using life insurance data.…”
Section: Life Insurance and Machine Learningmentioning
confidence: 99%
“…Clustering finds applications in various real-world scenarios, including market segmentation [1,2], healthcare [3,4], image processing [5][6][7], bioinformatics [8,9], social sciences [10], and text mining [11].…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish the K-modes algorithm from the K-means algorithm, there exist at least three characteristics concerning similarity metrics and how they represent the cluster: (1) The K-means algorithm employs means to represent the clusters, whereas the K-modes algorithm uses modes. (2) The K-means algorithm utilizes Euclidean distance, whereas the K-modes algorithm employs a dissimilarity metric.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that ML algorithms have proven extremely useful for addressing many predictions and classification problems with broad application scope, including customer classification and segmentation [5], market analysis [6], [7], and education [8]. Unfortunately, ML is relatively limited and very far from being used in real estate applications mainly in the Malaysian sense.…”
Section: Introductionmentioning
confidence: 99%